Distributional effects of minimum wages: Can unions expect a double dividend? A theoretical exercise from a supply-side view - Michael Öllinger; Christoph Ostermair; Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2019)
In this short communication, it is recalled that unions traditionally follow a policy of pushing higher average wages and at the same time propose a compression of the structure of wages and salaries, which follows the theory of some sort of equity. Considering a steep downfall of union density in many, if not all, OECD countries, the actual good condition for minimum wage policy comes as no surprise. Despite the fact that unions do not like the intervention of labor market policy at the cost of tariff autonomy, it can be shown that minimum wages are capable of serving both the above-discussed objectives of unions, but only the average wage rate cannot be increased. In addition, the distribution of wages will decrease, ceteris paribus. However, it is not clear whether minimum wages will be able to increase the overall wage quota in the economy. Here, this fact is theoretically explored in depth.
Keywords: J51; J38; J41; J58; 330; strategy of unions; wage dispersion; average and minimum wages; wage quota